2019
DOI: 10.1038/s41589-019-0413-4
|View full text |Cite
|
Sign up to set email alerts
|

A basic motif anchoring ISWI to nucleosome acidic patch regulates nucleosome spacing

Abstract: Recent studies have implicated the nucleosome acidic patch in the activity of ATP-dependent chromatin remodeling machines. We employed a photocrosslinking-based nucleosome profiling technology-'photoscanning'-to identify a conserved basic motif within the catalytic subunit of ISWI remodelers, SNF2h, which engages this nucleosomal epitope. This region of SNF2h is essential for chromatin remodeling activity in a reconstituted biochemical system and in cells. Our studies suggest that the basic motif in SNF2h play… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
69
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(74 citation statements)
references
References 58 publications
5
69
0
Order By: Relevance
“…5e, see H380, H2A89, and H2A113). Similar to our data, binding of the mammalian homolog of Isw1, Snf2h, to the acidic pocket is required to stimulate the remodeling activity of the ISWI complex by relieving auto-inhibition [16][17][18] . Two changes in ISW1a interactions with nucleosomes are required to deactivate ISW1a when remodeling mononucleosomes that are switched with dinucleosomes.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…5e, see H380, H2A89, and H2A113). Similar to our data, binding of the mammalian homolog of Isw1, Snf2h, to the acidic pocket is required to stimulate the remodeling activity of the ISWI complex by relieving auto-inhibition [16][17][18] . Two changes in ISW1a interactions with nucleosomes are required to deactivate ISW1a when remodeling mononucleosomes that are switched with dinucleosomes.…”
Section: Resultssupporting
confidence: 89%
“…The backtracking motion is only observed with ISW1a (not Isw1) on mononucleosomes and not on dinucleosomes. The importance of Isw1 contact with the acidic pocket of nucleosomes is consistent with the acidic patch of nucleosomes shown previously to be required for relieving auto-inhibition of mammalian ISWI and a part of the ISWI catalytic subunit outside of the ATPase domain to contact the acidic pocket [16][17][18] .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Despite these advances in recent years, some questions still need to be further answered, for example, how the remodeling activity of SMARCAD1 is activated by ubiquitinated nucleosomes or ssDNA and how SMARCAD1 removes the obstacles (such as 53BP1 and nucleosomes) through its histone dimer exchange activity. Take advantage of the recent advances in chemical protein synthesis ( McGinty et al, 2008 ; Fang et al, 2011 , 2012 ; Fierz et al, 2011 ; Siman et al, 2013 ; Li et al, 2014 , 2018 ; Morgan et al, 2016 ; Ai et al, 2019 ; Chu et al, 2019 ; Pan et al, 2019 ) and cryo-electron microscopy techniques, the biochemical and structural studies of ubiquitinated nucleosomes have recently received increasing attention ( Zhou L. et al, 2016 ; Anderson et al, 2019 ; Hsu et al, 2019 ; Jang et al, 2019 ; Park et al, 2019 ; Valencia-Sanchez et al, 2019 ; Worden and Wolberger, 2019 ; Worden et al, 2019 ; Xue et al, 2019 ; Yao et al, 2019 ; Dao et al, 2020 ). Both the in vitro reconstruction experiments and the structural analysis of the SMARCAD1-nucleosome complex may provide new insights into the remodeling mechanism of SMARCAD1.…”
Section: Discussionmentioning
confidence: 99%
“…6a). A recent study showed that ISWI also contains a small basic stretch C-terminal to the ATPase domain that mediates binding to the acidic patch 39 . This motif is conserved in ISWI orthologs and mutating it reduces the rate of remodeling, as we have reported here.…”
Section: Discussionmentioning
confidence: 99%